Considering Kingsolver’s “Great Barrier” for Beyond the Pastoral - Myers, Madison (The Trumpeter, 2019)
Looking at stories, we can begin imagining processes of reworlding, processes that involve un-learning and re-learning our relationships with the environment in a more-than-human world, and I wonder, too, if poetry can lead us to a similar place, poetry offering an approach toward a collaboration with the nonhuman in a more than human world. Barbara Kingsolver's poem, "Great Barrier," generally and broadly responds to climate change and the anxiety surrounding our limited amount of time to dramatically address climate change. I argue that she allows the potential for completely reimagining new practices and processes toward approaching the Anthropocene through the genre of poetry that does not return to something familiar.